Enhanced Transmission of Antibiotic Resistance in Campylobacter jejuni Biofilms by Natural Transformation - Bae, Junghee (Antimicrob Agents Chemother, 2014)
Campylobacter jejuni is a leading food-borne pathogen, and its antibiotic resistance is of serious concern to public health worldwide. C. jejuni is naturally competent for DNA transformation and freely takes up foreign DNA harboring genetic information responsible for antibiotic resistance. In this study, we demonstrate that C. jejuni transfers antibiotic resistance genes more frequently in biofilms than in planktonic cells by natural transformation.